2015
DOI: 10.1007/s10545-015-9897-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain dopamine‐serotonin vesicular transport disease presenting as a severe infantile hypotonic parkinsonian disorder

Abstract: Two male siblings from a consanguineous union presented in early infancy with marked truncal hypotonia, a general paucity of movement, extrapyramidal signs and cognitive delay. By mid-childhood they had made little developmental progress and remained severely hypotonic and bradykinetic. They developed epilepsy and had problems with autonomic dysfunction and oculogyric crises. They had a number of orthopaedic problems secondary to their hypotonia. Cerebrospinal fluid (CSF) neurotransmitters were initially norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 14 publications
3
37
0
Order By: Relevance
“…This mutation has previously been reported in another Saudi family who presented with global developmental delay, abnormal movement, hypotonia, and ataxia amongst other phenotypes but not microphthalmia . While the possibility of dual molecular diagnosis should be entertained, we note that only 3 patients have been reported with mutations in SLC18A2 making it possible that the phenotypic expression has not been fully elucidated yet . An unexpected discovery was made in patient 11DG0558, who presented with hypoplastic columella, flat nasal bridge and micropenis and colobomatous microphthalmia, in whom we found a splice site mutation in DSC3 (NM_001941.4:c.2236‐2A>G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This mutation has previously been reported in another Saudi family who presented with global developmental delay, abnormal movement, hypotonia, and ataxia amongst other phenotypes but not microphthalmia . While the possibility of dual molecular diagnosis should be entertained, we note that only 3 patients have been reported with mutations in SLC18A2 making it possible that the phenotypic expression has not been fully elucidated yet . An unexpected discovery was made in patient 11DG0558, who presented with hypoplastic columella, flat nasal bridge and micropenis and colobomatous microphthalmia, in whom we found a splice site mutation in DSC3 (NM_001941.4:c.2236‐2A>G).…”
Section: Resultsmentioning
confidence: 99%
“…An elegant series of experiments conducted by Rilstone et al showed that Pro387Leu results in severe, but not complete, loss of function . With only 3 cases reported to date, it will be interesting to see the varying phenotypes that are associated with the gene as additional mutations are discovered …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A defect in the glucose transporter Glut1 leads to microcephaly and seizures (Seidner et al 1998), a defect in the citrate transporter leads to an epileptic encephalopathy in the first days of life (Thevenon et al 2014), a defect in the thiamine transporter leads to encephalopathy and developmental delays (Kono et al . 2009), a defect in the dopamine-serotonin transporter leads to neonatal hypotonia and bradykinesis (Jacobsen et al 2016), and a defect in the manganese and zinc transporter affects brain growth and function, as well as bone mineralization (Boycott et al 2015). That the affected child in our study was found to have normal blood levels of biotin and pantothenic acid is not unexpected since the child was fed via a Broviac appliance.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Jacobsen et al reported that exome sequencing on infant twins with developmental delay, hypotonia and oculogyric crises (prolonged upward deviation of the eyes), revealed a SLC18A2 mutation, the mutation in these infants was p. pro237his. The twins also benefitted from treatment with a dopamine receptor agonist.…”
Section: Application Of Sequencing To Diagnosis Of Rare Diseases Likementioning
confidence: 99%